Both cationic and anionic redox chemistry in a P2-type sodium layered oxide. (March 2020) - Wang, Peng-Fei; Xiao, Yao; Piao, Nan; Wang, Qin-Chao; Ji, Xiao; Jin, Ting; Guo, Yu-Jie; Liu, Sufu; Deng, Tao; Cui, Chunyu; Chen, Long; Guo, Yu-Guo; et al.
Abstract: The demand for high energy Na-ion batteries has promoted intensive research on high energy oxygen redox chemistry in layered transition metal oxide cathodes. However, most layered cathodes with oxygen redox might suffer from irreversible electrochemical reaction, fast capacity decay and underlying O2 release. Herein, we report that copper element with a strong electronegativaty can stablize Na-deficient P2-Na2/3 Mn0.72 Cu0.22 Mg0.06 O2 phase to achieve both cationic and anionic redox chemistry. Hard and soft X-ray absorption spectra demonstrate that all Mn 3+ /Mn 4+, Cu 2+ /Cu 3+ and O 2− /(O2 ) n− participate in the redox reaction upon Na + ions extraction and insertion. Density functional theory (DFT) calculations confirm that the strong covalency between copper and oxygen ensures the cationic and anionic redox activity in P2-Na2/3 Mn0.72 Cu0.22 Mg0.06 O2 phase. The P2-Na2/3 Mn0.72 Cu0.22 Mg0.06 O2 cathode could deliver stable cycling life with 87.9% capacity retention at 1C during 100 cycles, as well as high rate performance (70.3 mA h g −1 cycled at 10C). Our findings not only provide a promising guidelines to enhance the electrochemical performance of layered oxides based on anionic redox activity, but also explore the potential science behind oxygen redox process. Graphical abstract: A new Na-deficient P2-Na 2/3 Mn 0.72 Cu 0.22 Mg 0.06 O 2 phase that shows both cationic and anionic activity using a strong electronegative copper element. The existence of strong covalency between copper and oxygen promises cationic and anionic redox chemistry upon solid-solution Na + ions extraction and insertion process. As a result, this phase could deliver stable cycling life in both Na-half cells and full Na-ion cells. Image 1 Highlights: A new Na-deficient P2-Na2/3 Mn0.72 Cu0.22 Mg0.06 O2 phase that shows both cationic and anionic activity. The existence of strong covalency between Cu 3d and O 2p orbitals promises cationic and anionic redox chemistry. This new Na-deficient P2-Na2/3 Mn0.72 Cu0.22 Mg0.06 O2 phase could deliver stable cycling life in both half and full Na-ion cells.